To Correlate Serum D-Dimer Levels With Clinical Outcome in Covid-19 Patients - Rajanna, Avinash Hanbe; K, Ravi; Shenoy, Vallish (International Journal of Innovative Research in Medical Science, 2021)
Background: The pandemic COVID19 has been causing significant morbidity and to some extent mortality as well. There has been urgent need to evaluate and identify the reliable predictors of disease severity and outcome. The fatal outcomes by COVID-19 are accompanied with micro vascular thromboembolism, which in turn is determined by serum D-dimer levels. Aim: To correlate serum D-dimer levels in COVID 19 patients admitted in an Indian setting, with clinical profiles and disease outcomes. Methods: A single-centre, observational, cross-sectional study was conducted among SARS-CoV-2 infected patients from March 2020 to May 2020. The diagnosis was confirmed by real-time polymerase chain reaction (RT-PCR). Serum D-dimer levels were compared with the treatment outcomes of the COVID-19 positive patients. Results: A total of 1977 COVID-19 patients were studied. The mean age was 43.89±15.58years and had male preponderance of 61.56% of the total subjects. The mean serum D-dimer levels among recovered and expired patients were 1.05±5.4mcg/ml and 1.81±2.92mcg/ml respectively. Conclusion: Serum D-dimer was increased in COVID-19 patients but did not show significant difference between the survival and the non-survival group, thus disproving it as a useful marker for assessing the severity of COVID-19.